2015
DOI: 10.1073/pnas.1504378112
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanism underlying β1 regulation in voltage- and calcium-activated potassium (BK) channels

Abstract: Being activated by depolarizing voltages and increases in cytoplasmic Ca 2+, voltage-and calcium-activated potassium (BK) channels and their modulatory β-subunits are able to dampen or stop excitatory stimuli in a wide range of cellular types, including both neuronal and nonneuronal tissues. Minimal alterations in BK channel function may contribute to the pathophysiology of several diseases, including hypertension, asthma, cancer, epilepsy, and diabetes. Several gating processes, allosterically coupled to each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 62 publications
0
35
0
Order By: Relevance
“…Studies of chimeric and mutant β subunits indicated that the cytosolic N- and C-termini of the BKβ1 subunit were crucial to altering the channel’s intrinsic opening and voltage-sensor activation (Orio et al, 2006; Wang et al, 2006). It was recently found that substituting two lysine residues (ie, K3 and K4) in the N-terminus of β1 can virtually abolish the effects of β1 on voltage-sensor activation (Castillo et al, 2015). The N-termini of the β2, β3a, and β3c subunits contain an inactivating domain which blocks the entrance to the intracellular pore and inactivates the BK channels (Li et al, 2007; Wallner et al, 1999; Xia et al, 1999, 2003; Zeng et al, 2003; Zhang, Zeng, Xia, & Lingle, 2009; Zhang, Zhou, Ding, Xia, & Lingle, 2006).…”
Section: Modulation Of the Bk Channel's Biophysical Properties By mentioning
confidence: 99%
“…Studies of chimeric and mutant β subunits indicated that the cytosolic N- and C-termini of the BKβ1 subunit were crucial to altering the channel’s intrinsic opening and voltage-sensor activation (Orio et al, 2006; Wang et al, 2006). It was recently found that substituting two lysine residues (ie, K3 and K4) in the N-terminus of β1 can virtually abolish the effects of β1 on voltage-sensor activation (Castillo et al, 2015). The N-termini of the β2, β3a, and β3c subunits contain an inactivating domain which blocks the entrance to the intracellular pore and inactivates the BK channels (Li et al, 2007; Wallner et al, 1999; Xia et al, 1999, 2003; Zeng et al, 2003; Zhang, Zeng, Xia, & Lingle, 2009; Zhang, Zhou, Ding, Xia, & Lingle, 2006).…”
Section: Modulation Of the Bk Channel's Biophysical Properties By mentioning
confidence: 99%
“…Rather, they usually alter several gating processes, which leads to modification of the channel’s response to physiological ligands, such as Ca 2+ i , and/or changes in macroscopic current kinetics (McManus et al, 1995; Brenner et al, 2000a; Cox and Aldrich, 2000; Nimigean and Magleby, 2000; Qian and Magleby, 2003; Orio and Latorre, 2005). For example, β1 subunit–induced changes in gating include modifications in intrinsic gating (i.e., gating in the absence of activating Ca 2+ i /voltage; Bao and Cox, 2005; Gruslova et al, 2012), stabilization of the slo1 voltage sensor in the active configuration (Bao and Cox, 2005; Contreras et al, 2012; Castillo et al, 2015), increased affinity for Ca 2+ in the RCK1 domain high-affinity Ca 2+ -sensing site when the channel is open, decreased affinity for Ca 2+ in the RCK2 domain Ca 2+ -sensing site when the channel is closed (Bao and Cox, 2005; Sweet and Cox, 2009), and increased allosteric coupling between Ca 2+ binding and channel opening (reviewed in Hoshi et al [2013]) while not modifying equivalent gating charge (Bao and Cox, 2005; Contreras et al, 2012; Castillo et al, 2015). The β1-dependent gating modifications lead to a significant increase in the channel’s apparent binding affinity for Ca 2+ i , which is evident by a decrease in the voltage needed for reaching half-value in the conductance (G)/maximal conductance plot (V 0.5 ) when ionic current behavior is evaluated at ≥1 µM Ca 2+ i (Cox and Aldrich, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Consistently with our hypothesis, γ1 and β3b induce the expected effects on the G-V curves of BK667CY channels, without altering the E-V curves, whereas β1 induces a leftward shift in the E-V curves. This shift on the voltage dependence of the E signal is preserved when BK667CY channels are coexpressed with the β3bNβ1 chimera, which affects VSD function without altering other parameters related to gating (50). Therefore, the voltagedependent component of the E signal seems to be related strictly to VSD function, as further demonstrated by the lack of effect of the γ1 subunit, which has been shown to shift the voltage dependence of gate opening by enhancing the allosteric coupling of voltage sensor activation without affecting VSD operation (36).…”
Section: Discussionmentioning
confidence: 99%
“…3b, right panel), similarly to the described modification (50). The structural determinants of the β1 subunit influence on the VSD reside within its N-terminus, which has been shown by engineering a chimera between the β3b subunit (which does not influence the VSD) and the N-terminus of the β1 (β3bNβ1) (50). We recapitulated this strategy.…”
Section: The Dynamics Of the Vsd Are Directly Reflected In The Gatingmentioning
confidence: 94%